SURGICAL APPROACH IN THE TREATMENT OF A LARGE RADICULAR CYST WITH PROMINENCE TOWARDS THE MAXILLARY SINUS - Lazarova, Marija; Arsovska, Mirjana Markovska; Gerasimova Pisevska, Sofijanka; Abdula, Erol; Mencheva, Zhaklina; Stojanova, Irena; Arsovski, Zoran; Chadikovska, Elizabeta (Journal of Morphological Sciences, 2025)
A cyst is defined as an epithelial lined pathologic cavity that may contain fluid or a semisolid material. The radicular cyst is an inflammatory odontogenic cyst seen at the root apex of dead pulp. These cysts are most common among other odontogenic cyst, may be because of high incidence of pulpal pathology in the oral cavity. Rarely the cyst can grow slowly to larger size causing destruction of adjacent vital structures. The aim of this paper is to present the surgical management of a large radicular cyst communicating with the maxillary sinus. This paper describes a case of a 42-year-old woman, where a radicular cyst was diagnosed clinically and radiographically. During the intervention, in addition to the removal of the cyst in toto, a sinus plasty was also performed, due to the prominence of the cyst in the maxillary sinus. The treatment of large radicular cysts is a problem that requires a serious approach in diagnostics, planning and performing the treatment. Pathohistological analysis is key in the correct diagnosis of odontogenic cysts. Key words: radicular cyst, maxillary sinus, sinus plasty, pathohystology.